Focus-sensitive operators in N?e?kepmxcin (Thompson River Salish) - Koch, Karsten; Zimmermann, Malte (Proceedings of Sinn und Bedeutung, 2019)
Based on new fieldwork data, this paper gives the first overview and analysis of focus sensitive operators in N?e?kepmxcin. Free foci in discourse exchanges are obligatorily marked using a predicative strategy, resulting in a clefting strategy for DPs. Exclusive and additive readings are expressed using the same predicative strategy, and we show that exclusive ??u? ‘only’ and additive ?e???u? ‘also, even’ are adverbial: as 2nd position clitics, they occupy a high functional projection in the left periphery. There is no specific marker of scalarity like English even. Finally, although exclusive ??u? is strictly f-sensitive in the sense of Beaver and Clark (2008), additive ?e???u? has the more flexible syntax and association behaviour of Q-adverbials like always.